Assessing climate change mitigation proposals for Malaysia: Implications for emissions and abatement costs. (20th November 2017) - Rasiah, Rajah; Al-Amin, Abul Quasem; Mintz Habib, Nazia; Chowdhury, Anwar Hossain; Ramu, Santha Chenayah; Ahmed, Ferdous; Filho, Walter Leal
Abstract: In accordance with the Paris Accord to cap global temperature rise to1.5°Celsius over the next 100 years, Malaysia submitted its Intended Nationally Determined Contribution (INDC) to the United Nations Framework Convention on Climate Change (UNFCCC) seeking to reduce emissions by 45% by 2030, which was changed to 2050 following the Marrakech Proclamation in 2016. This paper analyzes the implications of Malaysia's INDC and an additional proposal of continuing further climate control to cap temperature rise over the next century against the existing scenario in the country. The results show that the cumulative damage from climate change over the period 2010–2100 will amount to MYR2.1 billion under the present climatic regime. It will fall to MYR1.1 billion under scenario 2 and to MYR0.6 billion under scenario 3. Since the total abatement costs for scenario 2 (MYR14.3 billion) is close to that of scenario 3 (MYR14.6 billion) against the significant reduction in climate damage of the latter, the third proposal is the best alternative for Malaysia. Highlights: National economies are increasingly receptive to climate change mitigation policies. Effective prioritizing of climate change mitigation is important to reduce carbon emissions. Two climate change mitigation proposals are examined against no change scenario. Carbon emission reduction is assessed against abatement costs.